(untitled) (Research, Society and Development, 2020)
Objective: analyze the spatio-temporal distribution of Chikungunya fever incidence in Pernambuco state, Brazil. Method: the database was composed by Chikungunya fever epidemiological records in 2018, available through the Aggravation Notification Information System (SINAN) of Public Health Secretariat for Pernambuco State. The global and local Moran Index were used to assess Chikungunya spatial autocorrelation. Results: spatial distribution of Chikungunya fever clinical picture showed high concentration in state coast, with greater frequency and incidence rate in Cabo de Santo Agostinho and Escada municipalities. Clusters with positive spatial autocorrelation were formed between Cabo de Santo Agostinho and Vitoria de Santo Antão municipalities, revealing similar incidences. Conclusion: spatial analysis allowed to outline the epidemiological scenario for Chikungunya fever incidence, in 2018, consisting a tool capable of guiding strategic planning for epidemic control in Pernambuco.